2022
DOI: 10.1093/jxb/erac019
|View full text |Cite
|
Sign up to set email alerts
|

Auxin analog-induced Ca2+ signaling is independent of inhibition of endosomal aggregation in Arabidopsis roots

Abstract: Much of what we know about the role of auxin in plant development derives from exogenous manipulations of auxin distribution and signaling, using inhibitors, auxins and auxin analogs. In this context, synthetic auxin analogs, such as 1-Naphtalene Acetic Acid (1-NAA), are often favored over the endogenous auxin indole-3-acetic acid (IAA), in part due to their higher stability. While such auxin analogs have proven to be instrumental to reveal the various faces of auxin, they display in some cases distinct bioact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…We therefore visualized cytosolic calcium levels in the afb1 mutant using the R-GECO1 sensor 8 and vertical microfluidic microscopy 4 . The control line showed an almost immediate elevation in cytosolic calcium (calcium transient) in response to 150 nM IAA, as described before 1,9,10 (Fig. 2a, b).…”
Section: Resultssupporting
confidence: 78%
“…We therefore visualized cytosolic calcium levels in the afb1 mutant using the R-GECO1 sensor 8 and vertical microfluidic microscopy 4 . The control line showed an almost immediate elevation in cytosolic calcium (calcium transient) in response to 150 nM IAA, as described before 1,9,10 (Fig. 2a, b).…”
Section: Resultssupporting
confidence: 78%
“…However, evidence also supported that auxin could inhibit PM protein endocytosis at a high concentration (Paciorek et al, 2005; Robert et al, 2010), while IAA and 1‐NAA were also shown to promote the endocytosis of PIN2 but not PIN1, even at low concentrations (Narasimhan et al, 2021). The latter study demonstrated that high concentrations, but not low concentrations, of 1‐NAA inhibit PIN accumulation in BFA bodies (Wang et al, 2022). Therefore, to rule out the possibility that auxin affects the endomembrane system in the tmk1 single mutant, the localization of TGN/EE resident proteins, red fluorescent protein (RFP)‐tagged vacuolar H + ‐adenosine triphosphatase (ATP) subunit‐a1 (VHAa1‐RFP), GFP‐tagged syntaxin41 (SYP41‐GFP), and cyan fluorescent protein (CFP)‐tagged SYP61 (SYP61‐CFP), which are required for post‐Golgi trafficking were investigated (Uemura et al, 2004; Dettmer et al, 2006; Robert et al, 2008; Drakakaki et al, 2012).…”
Section: Resultsmentioning
confidence: 90%
“…As genetic screens require excellent uniformity of signals, it remains a challenge to overcome these disadvantages of cameleon and GCaMPs for the application to large‐scale genetic screens. Conceivably, reverse genetic approaches combined with cameleon/GCaMP Ca 2+ imaging could also be useful for the identification of Ca 2+ signaling‐related components, such as CNGC14 for auxin‐induced Ca 2+ increases (Shih et al ., 2015; Dindas et al ., 2018; Wang et al ., 2022). Given that stimuli higher than physiological levels have been used in Ca 2+ genetic screens, similar to other conventional genetic screens, the functions of these Ca 2+ signaling‐related components should be accessed and verified in planta under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%